Pelatihan Augmented Reality (AR) sebagai Media Pembelajaran Matematika yang Menyenangkan dan Interaktif di Kabupaten Maros - Arsyad, Nurdin; Djam'an, Nurwati; Alimuddin, Fauziyyah; Alimuddin, Alimuddin (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2025)
The advancement of digital technology offers significant opportunities to improve the quality of education, particularly in mathematics, which is often perceived as a difficult and tedious subject. One innovation that can be utilized is Augmented Reality (AR), which integrates virtual objects into real environments in real-time, making learning more engaging, interactive, and contextual. This community service activity was carried out in collaboration with the Mathematics Subject Teachers’ Forum (MGMP) of Maros Regency, aiming to enhance teachers’ competence in utilizing AR as a learning medium, to create a more enjoyable classroom atmosphere, and to provide alternative innovative teaching media. The implementation method consisted of three stages: socialization and introduction to AR, practice and learning simulation, and mentoring and evaluation. The results indicated an increase in teachers’ knowledge and skills in using AR, along with high enthusiasm when conducting AR-based mathematics learning simulations. Furthermore, the program was followed up with the signing of a Memorandum of Agreement (MoA) between the Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, and the Government of Maros Regency as a form of mutual commitment to support the implementation of AR in mathematics education at schools. Thus, this training has had a positive impact on improving the quality of teaching and students’ learning motivation, as well as serving as a strategic step in advancing educational innovation in the 21st century.